Identification of a p.Trp403* nonsense variant in PHEX causing X‐linked hypophosphatemia by inhibiting p38 MAPK signaling. Issue 7 (28th March 2019) - Li, Wei; Tan, Lingfang; Li, Xin; Zhang, Xiaoyu; Wu, Xiaoyan; Chen, Hongbo; Hu, Lihua; Wang, Xiaobei; Luo, Xiaoping; Wang, Fan; Xu, Chengqi; Chen, Qiuyun; et al.
Abstract: X‐linked hypophosphatemia (XLH) is the most common hereditary rickets, caused by mutations in PHEX encoding the phosphate regulating endopeptidase homolog X‐linked. Here, we report a nonsense variant in exon 11 of PHEX (c.1209G>A p.Trp403*) cosegregating with XLH in a Chinese family with a LOD score of 2.70. Real‐time reverse transcription polymerase chain reaction analysis demonstrated that p.Trp403* variant did not cause nonsense‐mediated mRNA decay (NMD), but significantly increased the expression level of FGF23 mRNA in the patients. Interestingly, p.Trp403* significantly reduced phosphorylation of p38 mitogen‐activated protein kinase (MAPK) but not ERK1/2. Moreover, overexpression of FGF23 significantly decreased phosphorylation of p38 MAPK, whereas knockdown of FGF23 by siRNA significantly increased phosphorylation of p38 MAPK. These data suggest that p.Trp403* may not function via an NMD mechanism, and instead causes XLH via a novel signaling mechanism involving PHEX, FGF23, and p38 MAPK. This finding provides important insights into genetic and molecular mechanisms for the pathogenesis of XLH.